Penetapan Hak Asuh Anak yang Lahir Akibat Pemerkosaan: Perspektif Maqashid al-Syari’ah - Firdaus, Muhammad Aulia; Iwan, Iwan (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
This study aimed to examine child rights and the requirements for custody determination for a child born as a result of rape based on the maqashid al-sharia perspective. This research employed a normative legal research method with the statute and comparative approaches. The collected legal materials were analyzed qualitatively to describe the problem and answer the research objectives. The results of this study indicate that maqashid al-sharia emphasizes the importance of guaranteeing hadhanah, or child custody, by considering the caregiver’s rights, the child’s rights, and the father’s or guardian’s rights. Furthermore, the Quran provides comprehensive guidance in protecting and fulfilling child rights, while the principles of maqashid al-sharia, such as hifz al-din, hifz al-nafs, hifz al-‘aql, hifz al-nasl, and hifz al-mal, serve as the foundation for fulfilling these rights. In cases of children born as a result of rape, maqashid al-sharia emphasizes the necessity of the state’s presence to protect the child through the mechanism of child custody determination through the courts, taking into account specific requirements, such as the age, health, and good conduct of the prospective guardian, to ensure proper care and the fulfilment of the child’s rights. Therefore, it is recommended that various parties, including the government, judges, and prospective guardians, synergize in protecting and fulfilling the rights of children born as a result of rape by the principles of maqashid al-sharia.